In vitro antiviral activity against rotavirus and astrovirus infection exerted by substances obtained from Achyrocline bogotensis (Kunth) DC. (Compositae) (2015)
Achyrocline bogotensis has been traditionally used to treat infections of skin, respiratory, tract urinary and other infections, but not to treat viral gastrointestinal disease. In this study, this Colombian native medicinal plant was investigated by its in vitro anti-rotavirus and anti-astrovirus activity. Several extracts and fractions phytochemically obtained from A. bogotensis were evaluated initially for their cell toxicity on MA104 and Caco2 cells and then for their anti-rotavirus (RRV) and anti-astrovirus (Yuc8) activity following three strategies: pre-treatment of cells (blocking effect), direct viral activity (virucidal effect) and post-treatment of infected cells (reduction of viral yield post-infection). In addition qualitative chemical studies were developed for the active compounds. Non-toxic concentrations of a fraction obtained exhibited antiviral activity against both viruses characterized by a virucidal effect and by the reduction of the infectious particles produced post-infection. Steroids, sterols, terpenes, phenols, flavonoids and sesquiterpenlactones were identified qualitatively in the active fraction. A. bogotensis contains substances with in vitro antiviral activity against rotavirus and astrovirus. This study confirms their anti-microbial properties and describes by the first time its antiviral activity in vitro.